Peace Pilgrim : her life and work in her own words - Compiled by some of her friends (Unites States of America : Friends of Peace Pilgrim, 1982)
Peace Pilgrim was the name adopted by Mildred Ryder when she began the first of her pilgrimages for peace in 1953. On January 1, 1953, at age 44, Mildred Norman Ryder adopted the name Peace Pilgrim, put on a pair of canvas sneakers, donned dark blue slacks, blouse, and a tunic - on which she had sown her new name - and set out to walk the length of the country leaving from Pasadena, California. Peace Pilgrim talked about peace among nations, between people and most important Inner peace. Penniless, walking with no organizational backing, Peace Pilgrim touched the lives and hearts of countless thousands of Americans. Some were charmed by her simple but cheerful presence, many others were profoundly inspired by her message and her remarkable lifestyle.